FAKTOR-FAKTOR YANG MEMPENGARUHI PENERIMAAN OPINI AUDIT GOING CONCERN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA TAHUN 2009-2011 (Students' Journal of Accounting and Banking, 2013)
This study aimed to analyze the effect of audit quality, financial condition, opinions auidt previous year, the growth of the company, and company size on a going concern audit opinion listed in Indonesia Stock Exchange. The population in this study are all companies listed on the Indonesia Stock Exchange in the year 2009-2011.The sample was selected using purposive sampling as many as 62 companies. Engineering test data is to use a multivariate analysis using logistic regression, the independent variable is a combination of metric and non-metric (nominal). Logistic regression models were used are as follows: to assess the feasibility of regression models, assessing model fit and parameter estimation, and interpretation.The analysis showed that the variables that have an influence on the audit opinion is going cocncern audit quality and firm growth. While the company's financial condition variable, the previous year's audit opinion, and firm size does not affect the going concern audit opinion.Keywords: quality audit, financial condition, previous year's audit opinion, the growth of the company, size of company, going-concern audit opinion.